2014
DOI: 10.3892/ijo.2014.2615
|View full text |Cite|
|
Sign up to set email alerts
|

The pterocarpanquinone LQB-118 induces apoptosis in acute myeloid leukemia cells of distinct molecular subtypes and targets FoxO3a and FoxM1 transcription factors

Abstract: Acute myeloid leukemia (AML) patients' outcome is usually poor, mainly because of drug resistance phenotype. The identification of new drugs able to overcome mechanisms of chemoresistance is essential. The pterocarpanquinone LQB-118 compound has been shown to have a potent cytotoxic activity in myeloid leukemia cell lines and patient cells. Our aim was to investigate if LQB-118 is able to target FoxO3a and FoxM1 signaling pathways while sensitizing AML cell lines. LQB-118 induced apoptosis in both AML cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…With the aim of developing new drugs, a series of compounds were designed and synthesized using the molecular hybridization of naphthoquinones and pterocarpans (5-7). The pterocarpanquinone LQB-118, the lead compound from this class, has antiprotozoal and anti-leukemic cell line activities, even in cells with an multidrug resistance phenotype (8)(9)(10). We have also demonstrated that LQB-118 is effective in treating experimental cutaneous leishmaniasis via oral delivery (11,12), and the death of Leishmania amazonensis parasites involved oxidative stress with hallmarks of apoptosis (13).…”
mentioning
confidence: 88%
“…With the aim of developing new drugs, a series of compounds were designed and synthesized using the molecular hybridization of naphthoquinones and pterocarpans (5-7). The pterocarpanquinone LQB-118, the lead compound from this class, has antiprotozoal and anti-leukemic cell line activities, even in cells with an multidrug resistance phenotype (8)(9)(10). We have also demonstrated that LQB-118 is effective in treating experimental cutaneous leishmaniasis via oral delivery (11,12), and the death of Leishmania amazonensis parasites involved oxidative stress with hallmarks of apoptosis (13).…”
mentioning
confidence: 88%
“…In addition to the more conventional chemotherapeutic drugs, the FOXO3 and FOXM1 transcription factors have emerged as the master regulators in novel molecular targeting anticancer agent resistance too. The pterocarpanquinone compound LQB-118 can induce apoptosis in drug-resistant myeloid leukaemic cells through specifically targeting FOXO3 and FOXM1[30]. Activation of FOXO3 has also been shown to reverse mitogen-activated protein/extracellular signal-regulated kinase kinase (MEK) 1/2 inhibitor AZD6244 chemoresistance in human cancer [31].…”
Section: Foxo3-foxm1: Chemotherapy and Resistancementioning
confidence: 99%
“…Multi-substituted naphthoquinones, including shikonin [35,36,37,38,39] and its derivative SH-7 [40], and other dihydroxy or dimethoxy 1,4-naphthoquinones [41,42], compared with mono- or di-substituted naphthoquinones, demonstrated superior in vitro activity against AML cells with IC 50 s ranging 0.1–4 μM. Heterocyclic monomeric naphthoquinones included furanonaphthoquinones FNQ3 [43] and FN6-one [44], β-lapachone [45,46,47,48,49] and nor-β-lapachone [45,46,50,51], dunnione [47], and pterocarpanquinone LQB-118 [28,52]. FNQ3 was significantly more effective than low dose cytarabine in reducing cell viability ( p < 0.001) and combining the two drugs led to an even greater reduction in cell viability in NB4 and U937 cells ( p < 0.01) [43].…”
Section: Resultsmentioning
confidence: 99%